2013
DOI: 10.1111/jfb.12209
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of movements by individual anadromous coastal cutthroat troutOncorhynchus clarkii clarkii

Abstract: Wild, downstream-migrating cutthroat trout, Oncorhynchus clarkii clarkii, smolts and adults were captured at a weir in Big Beef Creek, Hood Canal, Washington, surgically implanted with acoustic tags and tracked to identify spring and summer movements using stationary receivers in order to test the assumption that the species moves little while in marine waters. Overall, 93-96% migrated from the stream into the east side of the long narrow fjord, where they dispersed north and south along the shoreline. Most O.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The only exception to this pattern is the anadromous form of coastal cutthroat trout Oncorhynchus clarkii clarkii (Richardson 1836). Recent studies in the fjord‐like inlets of south Puget Sound and Hood Canal in Washington State, USA, have shed light on broad‐scale migratory patterns of anadromous O. c. clarkii (Goetz et al ., ; Losee et al ., ; Moore et al ., ) and demonstrated that they undergo short marine migrations relative to other Oncorhynchus spp. (Daly et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The only exception to this pattern is the anadromous form of coastal cutthroat trout Oncorhynchus clarkii clarkii (Richardson 1836). Recent studies in the fjord‐like inlets of south Puget Sound and Hood Canal in Washington State, USA, have shed light on broad‐scale migratory patterns of anadromous O. c. clarkii (Goetz et al ., ; Losee et al ., ; Moore et al ., ) and demonstrated that they undergo short marine migrations relative to other Oncorhynchus spp. (Daly et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic differences between the morphotypes (Goetz et al, 2010) result in higher lipid production in siscowets, resulting in 30-70% body fat composition compared to 20% in lean lake trout (Eschmeyer and Philips, 1965;Wang et al, 1990). Greater lipid levels may be adaptive for regulation of buoyancy in the deeper water and may facilitate DVM (Eshenroder and Burnham-Curtis, 1999;Goetz et al, 2013). Nitrogen is more soluble in fatty tissues than lean tissues, and greater lipid content may allow for quicker vertical migrations (changes in pressure) without associated barotrauma as a result of nitrogen escaping leaner tissues (Shilling et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, low biodiversity has been observed at sampling stations in Zone 2, close to the border between Zone 1 and 2, indicating a reduced selection of prey for sea trout in this habitat (Kroglund, Dahl, & Oug, 1998). Salmonids have shown great differences in movement rates contrasting day and night (Alanärä, Burns, & Metcalfe, 2001;Candy & Quinn, 1999;Eldøy et al, 2017;Goetz, Baker, Buehrens, & Quinn, 2013), and it has been shown for steelhead trout (Oncorhynchus mykiss) that horizontal movement rates increase twofold during daylight compared to night in the marine habitat (Ruggerone, Quinn, Mcgregor, & Wilkinson, 1990). There were significantly more excursions from the reserve during day than night, implying greater horizontal movement during day.…”
Section: Re Sultsmentioning
confidence: 99%